Detection of fibular rotational changes in cone beam CT: experimental study in a specimen model - Beisemann, Nils; Tilk, Antonella Maria; Gierse, Jula; Grützner, Paul Alfred; Franke, Jochen; Siewerdsen, Jeffrey H.; Vetter, Sven Y. (BMC medical imaging, 2022)
In syndesmotic injuries, incorrect reduction leads to early arthrosis of the ankle joint. Being able to analyze the reduction result is therefore crucial for obtaining an anatomical reduction. Several studies that assess fibular rotation in the incisura have already been published. The aim of the study was to validate measurement methods that use cone beam computed tomography imaging to detect rotational malpositions of the fibula in a standardized specimen model.
Gesehen am 07.12.2022